Correlation between Disclosure Status and Stress in Men who Have Sex with Men with HIV - Edianto Edianto; Agung Waluyo; Sri Yona; Ina Martiana (Jurnal Keperawatan Indonesia, 2020)
Men who have Sex with Men Living with HIV (MSM-LWH) experience psychological and social problems including depression, anxiety, fear of infecting others, frustration, and social isolation. In addition there are also problems in relationships due to fear of social stigma such as problems in marriage, conflict in the family, lack of family support, economic difficulties, and social rejection by the family. This research aims to assess the relationship between HIV status disclosure with stress in Men who have Sex with Men (MSM) living with HIV in Medan, Indonesia. This a cross-sectional study with convenience sampling technique were used. 176 respondents were MSM, HIV positive, and live in Medan city area. Data was collected by means of HIV Status Disclosure Questionnaires, and Perceived Stress Scale (PSS). In this research find that few 70.9% respondents had disclosed their status and about half reported stress. The disclosure of HIV status was significantly associated with Stress (P= 0,025). This study conclusions were HIV status disclosure can give negative effect for MSM living with HIV and becomes barrier to medical treatment and grow toward internal stress. Abstrak Hubungan antara Status Disclosure dengan Stres pada Lelaki yang Berhubungan Seks dengan Lelaki dengan HIV di Medan, Indonesia. Lelaki yang berhubungan seks dengan lelaki (LSL) yang hidup dengan HIV mengalami masalah psikologis dan sosial termasuk depresi, kecemasan, ketakutan menulari orang lain, frustasi dan isolasi sosial. Selain itu juga mengalami masalah dalam hubungan sosial karena takut akan stigma, konflik dalam keluarga, kurangnya dukungan keluarga, kesulitan ekonomi dan penolakan oleh keluarga. Penelitian ini bertujuan untuk mengetahui hubungan antara status disclosure HIV dengan stress pada LSL yang hidup dengan HIV di Medan, Indonesia. Metode yang digunakan adalah cross-sectional dengan menggunakan teknik convenience sampling. Sebanyak 176 responden LSL dengan HIV positif dan tinggal di wilayah kota Medan. Data dikumpulkan dengan menggunakan HIV Status Disclosure Questionare dan Perceived Stress Scale (PSS). Hasil penelitian menemukan bahwa sebanyak 70,9% responden memiliki status disclosure HIV rendah, sementara itu sebanyak 55,1% resonden mengalami stress yang tinggi. Status disclosure HIV secara bermakna dikaitkan dengan stress (p= 0,025; α= 0,05). Dapat disimpulkan bahwa status disclosure HIV dapat memberikan efek negatif pada LSL yang hidup dengan HIV dan menjadi penghalang untuk perawatan medis dan meningkatkan stress internal. Kata Kunci: HIV, status disclosure, lelaki yeng berhubungan seks dengan lelaki, stres